2009
DOI: 10.1142/s0217595909002286
|View full text |Cite
|
Sign up to set email alerts
|

Combining Process Selection and Lot Sizing Models for Production Scheduling of Electrofused Grains

Abstract: This work presents an optimization model to support decisions in the production planning and control of the electrofused grain industry. A case study was carried out in a Brazilian company with the aim of helping to increase productivity and improve customer service concerning meeting deadlines. A mixed integer linear programming model combining known models of process selection and single-stage lot sizing were applied to the production scheduling of electrofused grains. Optimizing this scheduling is not a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
16
0
5
Order By: Relevance
“…Another study examined the lot sizing and selection processes [19] to determine a production schedule that minimized shortages of items based on the choice of a production process over a certain period, where each process defined by the company is able to produce a mixture of products at different quantities.…”
Section: ) Limited Availability Of Multiple Resources;mentioning
confidence: 99%
See 2 more Smart Citations
“…Another study examined the lot sizing and selection processes [19] to determine a production schedule that minimized shortages of items based on the choice of a production process over a certain period, where each process defined by the company is able to produce a mixture of products at different quantities.…”
Section: ) Limited Availability Of Multiple Resources;mentioning
confidence: 99%
“…A mixed integer model is solved using general-purpose optimization software written in the GAMS modeling language, with a branch and cut method in the CPLEX solver. It is common for a production schedule to be modified several times in response to urgent orders and unexpected equipment failures, thus highlighting the importance of a modeling approach capable of generating efficient production programs in a feasible amount of time was adapted a mixed integer linear programming model to determine the production schedules for PPE [19]. The results from the model were compared to two existing practices used by the company, revealing that the model was effective and greatly improving the ability of the company to provide items on time.…”
Section: ) Limited Availability Of Multiple Resources;mentioning
confidence: 99%
See 1 more Smart Citation
“…The lot-sizing and scheduling problems have been widely used in several productive sectors (e.g., Araujo et al, 2008;Almada-Lobo et al, 2008;Luche et al, 2009;Toso et al, 2009;Santos & AlmadaLobo, 2012;Marinelli et al, 2007;Kopanos et al, 2010, among many others). Some studies are found in the production of non-alcoholic drinks such as soft drinks, water, tea and juice, but most of these studies consider soft drink production lines.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, o problema de dimensionamento de lotes nesses casos também deve investigar qual a escolha ideal de processos para encontrar a solução ótima. Em Luche et al (2009), foi tratado um problema real de planejamento e controle da produção de grãos eletrofundidos, em uma indústria brasileira que enfrenta dificuldades práticas para a obtenção de um planejamento factível, devido ao curto prazo de entrega e a pedidos adicionais que ocorrem semanal ou quinzenalmente. A esses fatores acrescentam-se o longo tempo de preparação de máquinas, permitidos apenas ao final do expediente diário, e uma caracterís-tica própria do problema desta empresa, em que cada processo resulta em quantidades distintas de diversos produtos, os quais são diferenciados pela granulosidade dos grãos eletrofundidos.…”
Section: Problema Com Múltiplos Processosunclassified